MORPHOLOGICAL AND RADIOLOGICAL ASPECTS OF POST-TRAUMATIC REMODELING OF THE MANDIBULAR BONE AFTER TRANSPLANTATION OF NATURAL COLLAGEN WITH LINCOMYCIN - Ilona Chelpanova (Acta Medica Leopoliensia)
This article presents the research results of the morphological, radiological, and lectin-histochemical characteristics of bone-ceramic regenerate after the transplantation of natural collagen combined with lincomycin into an experimental defect in the rabbit mandible.